2010
DOI: 10.1098/rspb.2010.1447
|View full text |Cite|
|
Sign up to set email alerts
|

Nutritional state and collective motion: from individuals to mass migration

Abstract: In order to move effectively in unpredictable or heterogeneous environments animals must make appropriate decisions in response to internal and external cues. Identifying the link between these components remains a challenge for movement ecology and is important in understanding the mechanisms driving both individual and collective motion. One accessible way of examining how internal state influences an individual's motion is to consider the nutritional state of an animal. Our experimental results reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 31 publications
3
62
0
Order By: Relevance
“…Despite such groups appearing similar in structure and form, there can often be greatly differing selection pressures that underlie the formation of groups. For example, vast mobile swarms of locusts are on a 'forced march' driven by limiting essential nutrients [47] and cannibalistic interactions [47][48][49].…”
Section: Resultsmentioning
confidence: 99%
“…Despite such groups appearing similar in structure and form, there can often be greatly differing selection pressures that underlie the formation of groups. For example, vast mobile swarms of locusts are on a 'forced march' driven by limiting essential nutrients [47] and cannibalistic interactions [47][48][49].…”
Section: Resultsmentioning
confidence: 99%
“…However, the situation is improving, due to technological advances in digital tracking and data processing, the empirical study of large scale collective motion in the field has become possible [17,220,54]. Furthermore, an increasing number of controlled laboratory experiments is being performed on collective motion of such different organisms as fish [1], insects [50,26], bacteria [321,322] or keratocytes (active tissue cells) [334]. The resulting data provide the foundation to address the question on actual properties of social interactions in real world swarms and flocks.…”
Section: Collective Dynamicsmentioning
confidence: 99%
“…This active fluctuations are a pure far-from equilibrium phenomenon and are relevant in the motion of an biological agents or artificial self-propelled particles. The origin of these fluctuations can be for example variations in the propulsion of chemically powered colloids [260,164,295], complex intra-cellular processes in cell motility [313,41] or unresolved internal decision processes in animals [245,195,26]. For example, the motion of a macroscopic animal moving in a homogeneous environment, where the fluctuations due the environment can be assumed as negligible, may nevertheless appear random to an external observer.…”
Section: Particles Driven By Active Fluctuationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequence of migration is a greatly increased chance of encountering fresh nutritional resources but, meanwhile, the crickets are 'travelling with their lunch' (Hansen et al 2011). Bazazi et al (2008Bazazi et al ( , 2011 subsequently showed that protein deprivation is also associated with enhanced marching in groups of cannibalistic desert locust nymphs.…”
Section: Cannibal Crickets and Locustsmentioning
confidence: 99%